Absorption Spectral Studies on Pr(III) and Nd(III) Metal Complexes with Schiff Base Ligand in Dioxane-water Media - Arora, Atul; Sharma, Anu; Mathur, Kirty; Mathur, R.P. (Asian Journal of Chemistry, 2010)
The interaction of Schiff base ligands, H2AD, H2AB, H2BD, H2BB and H2BA with Pr(Ill) and Nd(III) ion have been studied in different metal-ligand stoichiometry and pH in 20% dioxane-water medium. The absorption spectra have been recorded in visible range. The sharp bands in the spectra have been individually analysed by Gaussian curve analysis and various energy and intensity parameters such as Racah (Ek ), Slator-Condon (Fk), Lande (ζ4f), oscillator strength (P) and ludd-Ofelt parameter (Tλ) etc. have been computed using partial and multiple regression methods. The bonding parameter (b1/2) and nephalauxetic ratio (β) have been evaluated.